Cultural Identity and Symbolism in Qing Dynasty Zhangzhou Woodblock New Year Paintings: A Semiotic Analysis - Lin, Minghan; Chaipratoom, Jarun; Sriruksa, Kittisan; Wongthahan, Peerapong (Journal of Ecohumanism, 2024)
This research explores the cultural identity and symbolism of Zhangzhou woodblock New Year paintings from the Qing Dynasty through a semiotic lens. Such vibrant folk arts, derived from the cultural traditions of Zhangzhou, have become visible representations of the community's values, beliefs, and aspirations. The aim of the paper is to decode symbolic meaning from these patterns, motifs, and colors in those paintings toward the expression of the regional cultural identity. The use of the methodological framework for the study is from the theoretical basis of semiotics. This study provides qualitative research based on some paintings focused on iconography, color symbolism, and recurrence in motifs. The findings suggest that these artworks encapsulate essential spiritual, social, and agricultural values, which manifest themselves in themes such as religious devotion, familial harmony, and the cyclical nature of life tied to agriculture. Not only are these paintings decorative art, but they also serve as cultural artifacts that communicate the socio-economic and spiritual dimensions of Zhangzhou's identity in the Qing era. Preservation of such folk art thus would embody a way to continue the cultural heritage in this globalized world. The research helps to contribute to the understanding in which way art functions as a visual kind of language for cultural expression and preservation of identity.